Efek Media Terhadap Sosialisasi: Menjelajahi Peran Televisi dan Platform Media Baru - Febrimarani Malinda (Syntax Idea)
In the current digital era, mass media has a significant influence on the individual socialization process. Apart from television which has long been the main medium, new media platforms such as social media and other digital platforms are increasingly popular and have become an integral part of everyday life. The aim of this research is to explore the effects of media on socialization, with a focus on the role of television and new media platforms. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that television media and new media platforms such as social media have a significant influence on people's behavior and thought patterns. These media influence the way people communicate, obtain information, and form opinions. Social media also allows people to participate in discussions, share information, and influence the views of others. However, the use of social media can also directly influence social interactions, change the way people communicate, and influence people's thought patterns and behavior. Apart from that, social media can also influence social, cultural and norm changes in society.